Mesenchymal stem cells: diversity - O. M. Grabovyi; N. M. Nevmerzhytska; L. M. Yaremenko; H. B. Kostynskyi; A. S. Demydchuk; H. Yu. Kondaurova (Zaporozhye State Medical University, 2023)
Mesenchymal stem cells (MSCs) are diverse in terms of plastic, secretory and immunophenotypic features, which is due to the peculiarities of their genetic landscape. MSCs like other body cells are the result of the implementation of genetic information. However, some cells at different stages of histogenesis leave it. Such resident cells in tissues are stem cells. They are in a state of plastic quiescence and their genome does not undergo changes that would lead to commitment / differentiation. Although, these cells show a certain activity, producing various biologically active factors. It is logical to assume that the cells emerging from the process of histogenesis at its various stages will have different genetic landscapes, immunophenotypes and secretory potentials. The activation of MSCs occurs under conditions of physiological or reparative regeneration. Moreover, on the second hand it is explosive. Under natural conditions, the activation of MSCs during damage leads to their differentiation into fibroblasts and the formation of a connective tissue scar. But such consequences of reparation often come into conflict with the goal of treatment, when the task is not the formation of a scar, but the restoration of the parenchyma of the organ and its function. Therefore, the effects that will be obtained when using MSCs will depend on their initial state and methods of management. Aim. To analyze literature data on mesenchymal stem cells that reflect their ability to differentiate and secrete regulatory factors, immunophenotypic features and genetic landscape that may underlie their diversity. Conclusions. To obtain the desired result from the use of MSCs in regenerative medicine many factors must be taken into account. But data in this area is still fragmentary and often ambiguous. In addition, even taking into account the known factors in their various combinations is a very difficult task in the management of MSC. Given the unconditional priority of genetic and molecular research of MSCs the empirical method of studying the plastic and physiological properties of MSCs remains relevant today. It can just not create the basis for the development of the latest treatment methods, but also determine the direction of research in genetic and molecular research.